Implementation of Interactive Quiz-Based Formative Assessment through Quiz Whizzer in Article Text Learning - Wulandari, Ririn (Deiksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to determine the results of the assessment of article text material using Quiz Whizzer and to describe the challenges encountered during the implementation of formative assessment based on interactive quizzes through Quiz Whizzer. The subjects of this study were students of Class XII MIPA 3 at SMAN 4 Kota Cirebon. The research employed a narrative method with descriptive analysis techniques. The findings showed that the results of the formative test assessment in article text learning using Quiz Whizzer yielded an average score percentage of 58.08, which falls into the moderate category. However, the use of Quiz Whizzer presented several challenges, such as internet access issues, a ranking reduction system, the ability to access browser tabs—allowing students to search for answers online—and the risk of delayed participation in the quiz forum, which could result in students not joining the quiz